Reading Beyond Race in Margaret Laurence’s “The Loons” from A Bird in the House - Foster Stovel, Nora (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2010)
AbstractMargaret Laurence’s short story “The Loons” from A Bird in the House (1970) has proved highly controversial as an example of racist or anti-racist literature. The question is which? Laurence’s bifocal narrative technique allows the mature narrator Vanessa MacLeod to revise her childhood prejudices and satirize the racial stereotypes in her ten-year-old self’s perception of Piquette Tonnerre. Some critics have opined that, in the last sentence of the story, Laurence reinscribes the racism she has taken pains to deconstruct. Considering the story in context, however, suggests the focus of the story is the death of Vanessa’s father. Realizing Piquette shares her grief inspires Vanessa to view her, years later, as an individual. The loons, “those phantom birds,” prophesy death. Vanessa realizes Piquette, who suffered so greatly, “might have been the only one, after all, who had heard the crying of the loons.”